Administering Online Writing Assessments in English Language Teaching: Challenges and Solutions - Lailatul Abidah; Hartono Hartono (JURNAL ARBITRER, 2023)
In the digital age, assessment becomes one of the most important factors to consider when planning English courses virtually. In actuality, however, many English teachers struggle to manage and administer online writing assessments efficiently and successfully. This article will give a general overview of the difficulties associated with online writing assessments and their workable solutions. Qualitative principles of data gathering and analysis were applied to provide answers to the issues and served as valuable references. The finding reveals three main problems with online writing assessments: academic integrity, limited facilities and infrastructure, and a lack of digital literacy. However, despite the drawbacks of online writing assessments, students are gaining more benefits and knowledge in digitalizing education. Thus, practical solutions such as using task performance, particular strategies to overcome technical issues, and increasing teacher awareness of digital literacy must be properly implemented.